Rescue Operations During Incidents Involving Alternatively Powered Vehicles. Hydrogen Propulsion - Jan Kielin; Jacek Zboina; Grzegorz Bugaj; Jacek Zalech; Damian Bąk (Safety & Fire Technology, 2023)
Aim: This article presents key information and conclusions about hydrogen-powered motor vehicles, as well as technological equipment and technical infrastructure enabling the work of hydrogen fuel cells in the context of their fire safety, particularly the conduct of rescue operations. The authors’ main areas of consideration are the challenges for emergency services and the possible risks associated with the development and increasingly widespread and varied use of these technologies. Introduction: We are currently in the midst of the biggest energy crisis since the end of World War II. Therefore, the world’s leading economies are taking steps to intensify the production of alternative fuels – including hydrogen – and thus reduce the extraction of fossil fuels. One area of consideration and challenge related to increased extraction, processing and use of hydrogen is safety, particularly fire safety. In this regard, a major challenge is the knowledge, skills, equipment and facilities for rescue operations. Methodology: Based on a review and analysis of literature on the subject and available research results, key information, conclusions and recommendations directed to emergency services conducting operations during accidents and fires involving fuel cells were developed. Taken into account are the specific properties of hydrogen and the need to store it under high pressure. The article reviews the current state of knowledge regarding hazards and how to deal with them when conducting rescue operations during incidents involving hydrogen-powered vehicles. Conclusions: The development of this and other technologies, as well as the use of new alternative fuels, along with the increase in the number of vehicles powered in this way, will undoubtedly result in numerous and varied challenges for fire protection in the near future, including the need for rescue operations. These changes require systemic preparation and improvement of both the knowledge, skills of the rescuers and their equipment. Therefore, it is urgently necessary to work on the preparation/adaptation of appropriate education, training and professional development programs and teaching materials. It is necessary also to clarify the technical requirements for equipment for storing and supplying hydrogen to vehicles for example passenger vehicles and technical equipment in plants such as forklifts or generators for providing electricity in emergency situations. Work on these regulations is currently underway. Keywords: hydrogen drives, fire safety, rescue operations, rescue card